New Procedures by Microwave Field Assisted Extraction and Mineralization of Complex Samples for the Needs of Inorganic Elemental Analysis - Šídová, Tereza; Husáková, Lenka; Urbanová, Iva; Venclová, Jana; Svízelová, Monika; Ibrahimová, Lucie (Ing. Václav Helán - 2 THETA, 2018)
A large number of case studies are presented covering new approaches and new experiments, which meet the requirement for industrial application of sustainable chemistry. Nevertheless preparations of samples with complex matrix such as ZrO2, TiO2, sludge, phosphate fertilizers, fly ash, sediments, etc. still contains energy-intensive and time consuming steps or includes chemicals such as hydrofluoric acid for sample dissolution. By replacing highly toxic reagents with the employment of microwave assisted extraction (MAE) or digestion (MWD), simple and environmentally friendly methods were developed in accordance to current green chemistry trends.
Nové postupy mikrovlnným polem asistované extrakce a mineralizace komplexních vzorků pro potřeby anorganické prvkové analýzy
Keywords: Microwave-assisted extraction; Microwave-assisted digestion; Ammonium fluoride; Green chemistry; Mikrovlnným polem asistovaná extrakce; Mikrovlnná mineralizace; Fluorid amonný; Zelená chemie